Keberadaan Hak Kekayaan Intelektual Seni Batik Jambi di Kota Jambi - Syarifa Mahila (Universitas Batanghari Jambi, 2018)
Batik Artwork is a work in the field of Intellectual Property Rights which is more primarily included in the Copyright field. To product a piece of batik cloth, several processes are needed, so that a piece of batik cloth has the possibility of attaching several intellectual property rights other than copyrights.Batik Jambi business is one group of Small and Medium Industries (IKM) that develops in the City of Jambi. Based on data obtained from the Jambi City Office of Trade and Industry, in 2016 there were 98 units of Batik Jambi IKM, in 2017 there were 88 units of Batik Jambi IKM.Each IKM generally has no intellectual property rights. Only limited brands registered with the Trade and Industry Office as brands for registration of business licenses. This is because they still feel that they are not yet in line with the turnover they earn, while registration is certainly a cost.